Evaporation Behaviour of Biodiesel Droplets on Heated Wall Surfaces - Theebenraj Rajosagran; Muhammad Haikal Mukhtar; Favian Jikol; Mohd Zaid Akop; Yusmady Mohamed Arifin; Safarudin Gazali Herawan (International Journal of Integrated Engineering, 2026)
The rising demand for renewable energy sources has increased interest in biodiesel as a sustainable alternative to conventional diesel fuel. This study investigates the evaporation characteristics of diesel, pure biodiesel, and biodiesel blends using a Hot Surface Evaporation Test (ET) to simulate conditions similar to those inside a diesel engine. The main objective is to evaluate the influence of biodiesel concentration on evaporation behaviour when fuel droplets are deposited on heated aluminum surfaces. Key parameters examined include surface temperature, blend ratio, and droplet lifespan. Results reveal that higher biodiesel content leads to increased fuel film thickness and elevated boiling points, which collectively slow down the evaporation process. The Maximum Evaporation Point (MEP) for each fuel type was calculated and compared. These findings offer valuable insights into the combustion behaviour of biodiesel fuels and support their broader implementation in Malaysia’s transportation sector, aligning with the country’s renewable energy development goals. This work provides a foundation for future research into biodiesel combustion dynamics under engine-relevant conditions.